Genome-wide identification and expression profile of HIR gene family members in Oryza sativa L - Li, Jiahao; Shao, Lingyu; Wang, Qian; Shi, Liyu; Wu, Wei; Chen, Wei; Yang, Zhenfeng; Li, Saisai (Frontiers in Plant Science, 2024)
The hypersensitive-induced reaction (HIR) gene family is associated with the hypersensitive response (HR) in plant defense against pathogens. Although rice (Oryza sativa L.) is a crucial food crop, studies on its HIR genes are limited. This study identified six HIR members, categorized into three phylogenetic clades. The analyses of phylogenetics, gene structures, and collinear relationships revealed a high conservation of these genes, featuring the stomatin/prohibitin/flotillin/HflK/C domain.OsHIR genes were regulated by cis-acting elements, including ARE, SARE, DRE, LTR, and GARE. OsHIRs were widely expressed in multiple plant organs, including roots, stems, and leaves. These genes respond to various abiotic stresses (like drought and low temperature) and hormone treatments (including ABA, SA, GA, and MeJA)with overlapping yet distinct expression patterns. Our results indicate that OsHIRs are involved in abiotic stresses and hormone responses, which provides a basis for further functional analysis of OsHIRs in rice crop plants.